Comparison between thyroid stimulating immunoglobulin and TSH-receptor antibodies in the diagnosis and management of Graves’ disease - Yao, Peiwei; Xie, Yunliang; Wang, Yunlin; Liang, Chunyan; Huang, Bingwen (Frontiers in Endocrinology, 2024)
Introduction TSH-receptor antibodies (TRAb) directed against the TSH receptor (TSH-R) induce hyperthyroidism in patients with Graves′ disease (GD). TRAb detected by previous radioimmunoassay only reflects the presence of autoantibodies, but not the function of such antibodies. Thyroid stimulating immunoglobulins (TSI) is a relatively new method for assessing TSH-receptor antibodies function. The aim of this study was to investigate the role of TSI in the diagnosis and management of GD. Methods Patients with newly diagnosed GD (n=140, age 38.00 ± 11.99 years, 106 women) received pharmacological therapy (methimazole) up to 18 months in the outpatient or inpatient department of the Second People’s Hospital of Foshan City from January 2013 to December 2018. GD was identified by clinical signs and symptoms and relevant laboratory tests. Blood samples for TSI and TRAb and other thyroidal biomarkers were obtained at baseline and at three times during the follow-up. All patients with GD were followed up for at least 5 years to see if the patient was cured or had relapsed. Results TSI and TRAb in GD patients were significantly higher than those in the normal control group (P<0.001), and there was a strong correlation between TSI and TRAb in GD patients (P<0.001). After treatment, TSI and TRAb significantly decreased (P<0.05), TSI and TRAb in patients with disease course more than 2 years were significantly higher than those in patients with disease course less than 2 years (P<0.05), There was no statistically significant difference in TSI and TRAb at initial diagnosis between patients with a disease duration of more than 2 years and less than 5 years and those with a disease duration of more than 5 years (P>0.05); if the patients were still positive for TSI or TRAb antibodies at 5 years of follow-up after treatment with anti-hyperthyroidism medication, the patients were at a higher risk of relapse (P<0.001). Conclusion The higher TSI at the initial diagnosis of GD, the longer duration of treatment with anti-hyperthyroid drugs and the higher risk of relapse. Compared with TRAb, serum TSI level is also important in the clinical diagnosis and prognosis of GD, but which one is superior to the other needs further study.